2021
DOI: 10.13057/biodiv/d221231
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antibacterial, antifungal and antioxidant activities of Taxus baccata essential oil from Algeria

Abstract: Abstract. Benlembarek K, Lograda T, Ramdani M, Figueredo G, Chalard P. 2021. Chemical composition, antibacterial, antifungal and antioxidant activities of Taxus baccata essential oil from Algeria. Biodiversitas 22: 5475-5483. This work aims to study the chemical composition, the antibacterial, antifungal and antioxidant activities of Taxus baccata essential oil of Algeria. The essential oil was obtained by hydro distillation; its chemical composition was determined by GC and GC-MS analysis. The antibacterial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The suspension showed better pharmacokinetics in the intravenous mouse model, with a larger area under the curve (AUC) 0-∞ (20.343 ± 9.119 µg•h/mL vs. 5.196 ± 1.426 µg•h/mL) and a higher clearance rate compared to paclitaxel solution (2.050 ± 0.616 L/kg•h vs. 0.556 ± 0.190 L/kg•h), indicating the prepared water-soluble paclitaxel suspension had good bioavailability [78]. Additionally, studies have shown that Taxus essential oil exhibits certain antibacterial activities against both Gram-negative and Gram-positive bacteria [79,80], and a Chinese patent CN103285082A disclosed a drug composition for treating gynecological inflammation, combining Taxus extracts and essential oil with cocoa butter, semi-synthetic fatty acid glycerides, etc. The prepared suspension increases the drug action area due to its molecular characteristics, facilitating absorption, using a direct administration route, and with strong practicability.…”
Section: Liquid Dosage Formsmentioning
confidence: 99%
“…The suspension showed better pharmacokinetics in the intravenous mouse model, with a larger area under the curve (AUC) 0-∞ (20.343 ± 9.119 µg•h/mL vs. 5.196 ± 1.426 µg•h/mL) and a higher clearance rate compared to paclitaxel solution (2.050 ± 0.616 L/kg•h vs. 0.556 ± 0.190 L/kg•h), indicating the prepared water-soluble paclitaxel suspension had good bioavailability [78]. Additionally, studies have shown that Taxus essential oil exhibits certain antibacterial activities against both Gram-negative and Gram-positive bacteria [79,80], and a Chinese patent CN103285082A disclosed a drug composition for treating gynecological inflammation, combining Taxus extracts and essential oil with cocoa butter, semi-synthetic fatty acid glycerides, etc. The prepared suspension increases the drug action area due to its molecular characteristics, facilitating absorption, using a direct administration route, and with strong practicability.…”
Section: Liquid Dosage Formsmentioning
confidence: 99%
“…Whereas in the case of volatile oils obtained from fresh leaves, the chemical composition of all yew taxons is more similar. The chemical composition of the volatile oil obtained from the leaves of Taxus baccata species from Algeria was analyzed by Benlembarek et al (2021). The researchers identified by GC/MS analysis the following compounds in the highest concentrations: undecanon-2 (76.96%); nonanon-2 (5.57%); tridecanon-2 (4.43%); decanon-2 (3.92%); methyl dehydro-abietate (1.9%); α-pinene (1.13%).…”
Section: Qualitative Assessment Of Hydrosol Absorption Spectramentioning
confidence: 99%
“…Analyzing potassium ion efflux, the cited authors found that the K+ ion efflux of Gram-positive bacteria was 1.2 times higher than that of Gram-negative bacteria, stating that in bacterial cells treated with volatile oil, the loss of cytoplasmic constituents indicated significant and irreversible damage to the plasma membrane as a result of the action of volatile oil. In another of these studies Benlembarek et al (2021) tested the antibacterial and antifungal activity of T. baccata volatile oil; the pure extracted oil showed inhibitory action on the bacterial strain Pseudomonas aeruginosa (inhibition zone diameter of 15.3 mm) and the fungal strains Puccinia sp. (inhibition zone diameter 15.07 mm), Fusarium oxysporum (inhibition zone diameter 14.05 mm), Alternaria alternata (inhibition zone diameter 13.14 mm), Fusarium graminum (inhibition zone diameter 12.14 mm).…”
Section: Qualitative Assessment Of Hydrosol Absorption Spectramentioning
confidence: 99%
See 1 more Smart Citation